Prostate cancer and elective nodal radiation therapy for cN0 and pN0 - a never ending story?: Recommendations from the prostate cancer expert panel of the German Society of Radiation Oncology (DEGRO) - Körber, Stefan A.; Höcht, Stefan; Aebersold, D.; Albrecht, Clemens; Rogner, Danielle; Ganswindt, Ute; Schmidt-Hegemann, Nina-Sophie; Hölscher, T.; Müller, A.-C.; Niehoff, Peter; Peeken, Jan Caspar; Pinkawa, Michael; et al. (Strahlentherapie und Onkologie, 2024)
For prostate cancer, the role of elective nodal irradiation (ENI) for cN0 or pN0 patients has been under discussion for years. Considering the recent publications of randomized controlled trials, the prostate cancer expert panel of the German Society of Radiation Oncology (DEGRO) aimed to discuss and summarize the current literature. Modern trials have been recently published for both treatment-naïve patients (POP-RT trial) and patients after surgery (SPPORT trial). Although there are more reliable data to date, we identified several limitations currently complicating the definitions of general recommendations. For patients with cN0 (conventional or PSMA-PET staging) undergoing definitive radiotherapy, only men with high-risk factors for nodal involvement (e.g., cT3a, GS ≥ 8, PSA ≥ 20 ng/ml) seem to benefit from ENI. For biochemical relapse in the postoperative situation (pN0) and no PSMA imaging, ENI may be added to patients with risk factors according to the SPPORT trial (e.g., GS ≥ 8; PSA > 0.7 ng/ml). If PSMA-PET/CT is negative, ENI may be offered for selected men with high-risk factors as an individual treatment approach.